2018
DOI: 10.1021/acs.jpcc.8b06555
|View full text |Cite
|
Sign up to set email alerts
|

Guaiacol Adsorption and Decomposition on Platinum

Abstract: Guaiacol (2-methoxyphenol, C6H4(OH)­(OCH3)) adsorption and reactions on a Pt(100) surface were studied with infrared reflection–absorption spectroscopy (IRAS) and temperature programmed desorption (TPD) measurements at different surface coverage values from 100 to 800 K. In addition, density functional theory (DFT) calculations were used to determine geometries, adsorption energies, and vibrational frequencies for adsorption structures. Depending on surface coverage, guaiacol formed one or two physisorbed stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…As shown in Figure 4 a, the hydroxyl absorption band of EMP in the first stage δ (C–OH) was located at 1366.73 cm –1 , while it disappeared in the spectra of EMP-Na and Prod-S1. 28 It indicated that a neutralization reaction occurred in the first stage. To further illustrate the occurrence of the acid–base reaction, the infrared spectra of EMP, Prod-S1, and EMP-Na were further compared in Figure 4 a.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4 a, the hydroxyl absorption band of EMP in the first stage δ (C–OH) was located at 1366.73 cm –1 , while it disappeared in the spectra of EMP-Na and Prod-S1. 28 It indicated that a neutralization reaction occurred in the first stage. To further illustrate the occurrence of the acid–base reaction, the infrared spectra of EMP, Prod-S1, and EMP-Na were further compared in Figure 4 a.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly constructed periodic surfaces with similar computational settings were previously used successfully for studying adsorption and reactions on Ni [13] and other metal surfaces. [14][15][16][17][18][19][20][21][22][23] Adsorption energies were calculated at 0 K without zero-point energy corrections using as a reference the sum of energies for the corresponding clean surface and an isolated propylene molecule calculated separately. Adsorption energies are reported as positive numbers, À ΔE ads .…”
Section: Methodsmentioning
confidence: 99%
“…The remaining two bottom layers were constrained at the bulk Ni positions, accounting for the bulk structure. Similarly constructed periodic surfaces with similar computational settings were previously used successfully for studying adsorption and reactions on Ni [13] and other metal surfaces [14–23] …”
Section: Methodsmentioning
confidence: 99%
“…The density of states was calculated with 1 empty band and a k-point grid of 2 Â 2 Â 1.The computational settings were similar to those that were previously used successfully to describe molecular properties of surface functional groups, including hydroxyls. [54][55][56][57][58] The rGO structure was modeled as an infinite slab constructed using a periodic unit cell. Edge sites were not considered in the model because they represented less than 0.2% of all carbon atoms due to the large size of our rGO sheets (300-800 nm).…”
Section: H Dispersion-corrected Density Functional Theory (Dft-d) Calculationsmentioning
confidence: 99%